Korelasi Media Boneka Kaus Kaki dengan Media Wayang Kertas Terhadap Sikap Sosial Siswa Sekolah Dasar - Erwin Putera Permana (Jurnal Simki Economic, 2021)
The purpose of this research is to describe the correlation of the role of sock puppet media and paper puppet media on the social attitudes of elementary school students. The independent variable is sock puppet media and paper puppet media, while the dependent variable is students' social attitudes. The research technique used is Quasi Experimental Design. The instruments developed for this research are learning tools for the experimental class and control class, social attitude questionnaires for students and observer sheets for teachers. In this study, the social attitudes studied were 1) responsibility, 2) tolerance, 3) mutual cooperation, 4) cooperation and 5) discipline. The use of sock puppet media and paper puppet media is very good, this is evidenced by the acquisition of scores of the experimental class of students in the class, which amounted to 20 students in the very good category and the control class scores 61, 61.5, 62.5, 64, 66 and 66.5. The results of the analysis of the social attitude scores of the control class students showed that students in this class had good social attitudes, as evidenced by the acquisition of a student score of 16 students in the good category and a student score of 4 students in the very good category.